Validity and reliability of the Duruöz Hand Index in patients with lateral epicondylitis - İbrahim Taka and Berat M. Alkan and Fatma F. Yıldız (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the validity, reliability and clinimetric features of the Duruöz Hand Index (DHI) in patients with lateral epicondylitis. Patients and methods: Between October 2019 and January 2020, a total of 78 patients (28 males, 50 females; mean age: 46.4±9.4 years; range, 20 to 65 years) who presented with pain in the forearm and were diagnosed with lateral epicondylitis were included in the study. The patients were evaluated using the Visual Analog Scale (VAS), Health Assessment Questionnaire (HAQ), the Patient-Rated Tennis Elbow Evaluation Questionnaire (PRTEEQ), the Disabilities of the Arm, Shoulder and Hand (DASH) Questionnaire at Weeks 0, 1 and 4. The DHI reliability (Cronbach alpha, intraclass correlation [ICC]), validity and factor analyses were performed with the data of 70 and 49 patients who attended to follow-up visit at Weeks 1 and 4. The effect size (ES), standard response mean (SRM), and minimum detectable change (MDC) values of the DHI were calculated. Results: Of the patients, 84.6% were right-handed. The ICC coefficients of DHI were found to be perfect with the test-retest method (ICC; total=0.943). It showed a well-excellent consistency with the internal consistency method (Cronbach alpha; total=0.90). In the structural validity of the DHI, it was very strongly correlated with the DASH (r=0.801; p<0.01), strongly correlated with the PRTEEQ and HAQ total scores (r=0.793; p<0.01; r=0.785; p<0.01), and acceptably correlated with PRTEEQ pain score (r=0.570; p<0.01). The DHI was acceptably correlated with the VAS and grip strength as measured by the hand dynamometer (p<0.05). In our study, three main factors were obtained and MDC and responsiveness sensitivity were found to be moderate (MDC=4.4; SEM=1.61; ES=0.246 p<0.001; SRM=0.538 p<0.001). Conclusion: Duruöz Hand Index is a reliable, valid, and practical functional assessment scale in patients with lateral epicondylitis.